The hydrophobicity of Ni–Fe alloy electrodeposits obtained at different current densities. (4th July 2017) - Torabinejad, V.; Aliofkhazraei, M.; Rouhaghdam, A. Sabour; Allahyarzadeh, M.H.
Abstract : A simple one-step method was used to fabricate a hydrophobic surface by electrodepositing Ni–Fe coating on low carbon steel at various current densities ranging from 2 to 6 A dm −2 . The as prepared coatings were hydrophilic showing a water contact angle (CA) of zero. After 17 days exposure of the coatings in ambient air, the wettability of the Ni–Fe coatings changed to hydrophobic. Increasing the current density of electrodeposition from 2 to 6 A dm −2 led to a reduction in the CA. The hydrophobic behavior of the Ni–Fe coatings after storage in air is related to two factors including the formation of airborne hydrocarbon compounds and the micro/nano pinecone-like structure of the Ni–Fe coating. Polarization tests and electrochemical impedance spectroscopy measurements indicated that the hydrophobic surfaces had higher corrosion resistance in comparison to the as-deposited coatings.